Cost-effectiveness of omalizumab for the treatment of inadequately controlled severe allergic asthma in Chinese children. (2nd January 2020) - Zhou, Hua; Lu, Yanming; Wu, Bin; Che, Datian
Abstract: Objective: The addition of omalizumab to standard therapy has proven to be efficacious in children with severe allergic asthma. The goal of this study was to assess the cost-effectiveness of adding omalizumab to standard treatment for asthma in Chinese pediatric patients. Methods: A Markov model was constructed to project the health and economic outcomes in pediatric patients with severe allergic asthma. Model inputs were obtained from the literature. Cost and quality-adjusted life-years (QALYs) were measured over a five-year time horizon. One-way and probabilistic sensitivity analyses were conducted. Results: For the base-case analysis, the addition of omalizumab to standard therapy yielded an incremental cost of 49, 047 for 0.232 incremental QALY, led to an incremental cost-effectiveness ratio of 211, 217/QALY. Sensitivity analyses were robust for these results. Conclusions: This study found that the addition of omalizumab is not a cost-effective strategy compared with standard therapy for children with severe allergic asthma in China due to its high cost.